ANALISIS SEKTOR EKONOMI UNGGULAN TERHADAP PEREKONOMIAN KABUPATEN SUMBAWA - Fahlia Fahlia; Rezki Ramdhany; Taufur Abdurrahman (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to identify and analyze the leading economic sectors of the economy in Sumbawa Regency. The research method used in this study is a quantitative analysis method, namely a research method with objects in the form of numeric data or numbers. The population is all data on the Gross Regional Domestic Product (GRDP) of Sumbawa Regency from the Central Statistics Agency (BPS) of the Province of West Nusa Tenggara. The samples taken are the 2015-2019 time series of the Gross Regional Domestic Product (GRDP) at constant prices according to business fields in Sumbawa Regency. The results of this study show that 8 basic sectors have a value of more than one, then 14 sectors have prominent growth both at the provincial and district levels and 8 sectors which are leading sectors.